Preparation of Nanosilver and Nanogold Based on Dog Rose Aqueous Extract - Jolanta Pulit; Marcin Banach (Bioinorganic Chemistry and Applications)
This paper describes a process of obtaining nanosilver and nanogold based on chemical reduction using substances contained in the aqueous extract of dog rose (Rosa canina). The resulting products were subjected to spectrophotometric analysis (UV-Vis), and testing of the nanoparticles’ size and suspension stability was carried out by measuring the electrokinetic potential, ζ, via dynamic light scattering (DLS). Solid samples were imaged by scanning electron microscopy (SEM). The obtained data were given to statistical analysis in order to illustrate the properties of the suspension depending on the values of the input parameters: metal salts concentration, pH of the reaction mixture, and process temperature. In the course of the work, samples of nanosilver and nanogold were obtained, which were stable for over two months and which had a monomodal particle size distribution.